Social media engagement behavior: A framework for engaging customers through social media content. (7th October 2019) - Dolan, Rebecca; Conduit, Jodie; Frethey-Bentham, Catherine; Fahy, John; Goodman, Steve
Abstract : Purpose: Organizations are investing heavily in social media yet have little understanding of the effects of social media content on user engagement. This study aims to determine the distinct effects of informational, entertaining, remunerative and relational content on the passive and active engagement behavior of social media users. Design/methodology/approach: Facebook Insights and NCapture are used to extract data from the Facebook pages of 12 wine brands over a 12-month period. A multivariate linear regression analysis investigates the effects of content on consuming, contributing and creating engagement behavior. Findings: Results reveal distinct effects of rational and emotional appeals on social media engagement behavior. Rational appeals in social media have a superior effect in terms of facilitating active and passive engagement among social media users, whereas emotional appeals facilitate passive rather than highly active engagement behavior, despite the social and interactive nature of the digital media landscape. Research limitations/implications: Results contribute directly to understanding engagement and customer experience with social media. Further theoretical and empirical examination in this area will aid in understanding the dynamic nature of the levels of engagement within social media. Practical implications: Findings provide managers and practitioners with guidelines and opportunities for strategic development of social media content to enhance engagement among consumers in a social media forum. Originality/value: This study is one of the first to empirically examine the construct of social media engagement behavior. It extends the utility of dual processing theory to demonstrate how rational and emotional message appeals result in online engagement.